Could Mindful Meditation be a Routine Therapeutic Intervention in Practice? - Gupta, Jones (Science Insights, 2024)
Although mindfulness meditation has become more and more well-liked as a therapeutic technique in recent years, it might not be appropriate for every person or situation. Although mindfulness meditation has been shown to be beneficial for reducing stress, anxiety, and depression, its effects may not be felt by all people. Furthermore, some people could find it challenging to practice mindful meditation because of a variety of obstacles, like attentional or cognitive impairments. It is pivotal to consider the unique demands of every client in a professional context and design interventions accordingly. It’s also critical to understand that, where appropriate, mindful meditation should be utilized in addition to other evidence-based therapies rather than being viewed as a one-size-fits-all remedy. Because of this, mindful meditation should not be used as the only therapeutic intervention in practice, even if it can be a useful tool in increasing mental well-being.